ҚАРАҚАЛПАҚ ТИЛИ ҲӘМ ӘДЕБИЯТЫ САБАҒЫН ОҚЫТЫЎДА ОҚЫТЫЎШЫЛАРДЫҢ АЎЫЗЕКИ СӨЙЛЕЎ ҲӘМ ЖАЗБА ТИЛИН РАЎАЖЛАНДЫРЫЎ МЕТОДИКАСЫ - Қабулова, М. (FAN va JAMIYAT, 2021)
The article focuses on the importance of developing students' oral and written language in the teaching of Karakalpak language and literature. The teaching of Karakalpak language and literature in schools is considered to be a combination of oral and written language, which has two different forms of communication between people. The article is aimed at enriching the spiritual culture of students.